Modern view on hepatic encephalopathy: basic terms and concepts of pathogenesis - T. V. Shulyatnikova; V. A. Shavrin (Patologìâ)
Background. The problem of acute and chronic forms of hepatic encephalopathy (HE) is not clearly identified among modern problems of hepatology and neuroscience in Ukraine. Despite the significant contribution to the development of lethal complications in patients with liver pathology and long history of the study of this issue, there is still no unified opinion on the links of HE pathogenesis.